Recenser, soutenir, agir - Alix (Alix, 2023)
Alix est là pour te soutenir ainsi que toutes les personnes qui interviennent auprès des personnes LGBTQ+ victimes de violence. Alix t’offre aussi des outils d’informations et de sensibilisation…
Keywords: Coffre à outils; À ajouter

Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Keywords: Bibliographie

Capsule sur le GRIP, projet Spotlight (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Capsule Collectif Social - Formation ADISQ (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'Aparté - Formation ADISQ (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

Accueil (Centre pour les victimes d’agression sexuelle de Montréal, 2023)
Le CVASM offre un soutien essentiel aux personnes touchées par la violence sexuelle depuis 1980. Trouvez de l'aide dès maintenant.
Keywords: Coffre à outils; À ajouter

Prévenir et gérer le harcèlement - Formations AQPM (Formations : Des classes de perfectionnement pour les professionnel-(le)s de l'industrie audiovisuel, 2023)
« Cette formation permettra aux producteurs et à leurs représentants de reconnaître les situations de harcèlement ou celles qui sont à risque de le devenir afin de comprendre les rôles et responsabilités qui leur reviennent. Les particularités propres à notre industrie y seront également abordées. Formateur: Me Frédéric Massé Borden, Ladner, Gervais »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Écouter, informer, soutenir - Info-aide violence sexuelle (2023)
De l'écoute, du soutien et des références pour les victimes d’agression sexuelle, d’exploitation sexuelle et de toute autre forme de violence sexuelle.

Violences sexuelles: Le plan d’action des festivals - Trépanier, Marilou Bayard (La Presse, 2023)
Les allégations d’intoxication au GHB au Festi-Plage de Cap-d’Espoir, l’an dernier en Gaspésie, ont secoué les festivals partout au Québec. Elles ont aussi servi de bougie d’allumage : alors que les services sont implantés depuis quelques années à Montréal, le milieu festif en région se mobilise pour soutenir les victimes d’agressions et de harcèlement sexuels.

Accusations d’agression sexuelle et de diffamation: Jasmin Roy réplique et poursuit en diffamation Jean-François Robillard - Dussault, Lila (La Presse, 2023)
Un duel de poursuites en diffamation est en cours entre l’acteur Jasmin Roy et un homme qui l’accuse d’agression sexuelle, Jean-François Robillard. L’affaire a pris racine dans la foulée du mouvement #metoo, en 2020. Elle remonte à une soirée dans un bar d’Abitibi-Témiscamingue, 20 ans plus tôt.
Keywords: Bibliographie; Nettoyer

The art of Jane Orleman: childhood trauma and the discourse of sexual violence - Kwon, Hyunji (Journal of Gender Studies, 2023)
Jane Orleman (American, born 1942) is an artist and a survivor of child sexual abuse. Through paintings she created during therapy, Orleman rejects the gendered and patriarchal binaries between therapeutic art and professional art, which pit the private, feminine, and intuitive against the public, masculine, and intellectual. By analysing selected artworks from Orleman that embody her child self, young woman self, and alternative self, I propose that Orleman reflects on and challenges the pathology of sexual trauma along with the discourse of sexual violence as a political statement. Therefore, I argue that her art deserves to be part of a larger, counternarrative, anti-rape and anti-incest cycle in contemporary American art.
Keywords: Sexual violence; art; survivor; therapy; trauma

Le délicat retour d’Éric Lapointe - Lemieux, Marc-André (La Presse, 2023)
Tapis rouge, apparition télé, concerts, nouvelle chanson, sortie d’album… Trois ans après avoir plaidé coupable pour voies de fait contre une femme et s’être éclipsé des grands circuits, Éric Lapointe retrouve, lentement mais sûrement, les projecteurs en 2023. Une opération fragile et non sans écueils possibles.

Un projet pilote pour réduire les risques d’intoxication et pour prévenir la consommation excessive (Éduc'alcool, 2023)
Montréal, le 21 avril 2023 – Éduc’alcool et le Service de police de la Ville de Montréal (SPVM) ont lancé hier le projet pilote Touche pas à mon verre* en présence du ministre de la Sécurité publique du Québec, M. François Bonnardel. Cette initiative prend la forme d’une distribution gratuite de 10 000 protège-verres afin de, notamment, […]
Keywords: Bibliographie; Dans le rapport; Nettoyer

The sound of misogyny: sexual harassment and sexual violence in the music industry - McCarry, Melanie; Käkelä, Emmaleena; Jones, Cassandra; Manoussaki, Kallia (Journal of Gender-Based Violence, 2023)
The cultural and creative industries are the fastest growing industries in the UK (). Stakeholder engagement, media reporting, anecdotal evidence and emerging research suggests that there are endemic levels of sexual harassment and sexualised violence within the music industry that can be described as widespread, systemic and normalised. This article reviews the literature on sexual harassment and sexualised violence in the music industry, examining gender stratifications and inequalities within the music industry with a focus on UK, Australian and US studies. The music industry is not a singular entity but instead, is an agglomeration of many different sub-sectors predominantly consisting of three interconnected spheres of music recording and distribution, music publishing and licensing, and live performance. This paper references Kelly’s (; ; ) theorisations on conducive contexts and the continuum of violence to argue that historical and entrenched misogyny and sexism along with the lack of regulation, process and governing frameworks create conditions for both the maintenance of gender inequality and the perpetuation of sexual harassment and sexualised violence within the music industry. Consequently, both the cultural context and the practice of misogyny (in this case sexual harassment and sexualised violence) within the music industry are mutually supporting and reinforcing.
Keywords: Misogyny; Music; Myriam

Analyse critique du discours en ligne sur les dénonciations de violences à caractère sexuel : le cas de la liste de potentiels agresseurs, Dis son nom - Pelletier, Michela (Université du Québec à Montréal, 2023)
Les fils de commentaires sur Facebook permettent aux internautes de s’exprimer sur différents enjeux. Dans le cadre de ce mémoire, les fils de commentaires sous des articles médiatiques provenant de trois journaux (Journal de Montréal, Le Devoir et La Presse) trainant de la liste de présumés agresseurs Dis son nom ont été analysés. À partir d’une analyse critique de discours, 201 commentaires en réaction à 13 articles médiatiques ont été étudiés afin de répondre à la question de recherche suivante : « Quelles sont les représentations dominantes des dénonciations de violences à caractère sexuel sur les réseaux sociaux dans les commentaires Facebook en réaction aux publications d’articles médiatiques concernant la liste de potentiels agresseurs Dis son nom ? ». De ce fait, l’analyse critique de discours a permis l’étude des représentations dominantes au sein des commentaires Facebook au sujet des dénonciations de violences sexuelles sur les réseaux sociaux. Les résultats de la recherche ont relevé que les discours ont des perspectives davantage négatives au sujet des dénonciations en ligne et que la majorité de ces commentaires ont été partagés par des internautes identifiés comme hommes. L’analyse a illustré que certains commentaires soulignent une transformation et une déconstruction des discours hégémoniques en matière de genre, en permettant notamment une prise de parole émancipatrice. Néanmoins, la plupart des commentaires reproduisent ces discours hégémoniques. L’analyse a également permis de saisir les rapports de pouvoir présents dans les discours, de relever les implicites, les non-dits et les paradoxes, en plus de certains stéréotypes de genre liés aux violences sexuelles au sein des commentaires. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Dis son nom, Facebook, commentaire(s), réseaux sociaux, violences à caractère sexuel, violence(s) de genre, victime(s), #MoiAussi, culture du viol, Analyse critique de discours

Au-delà des « vagues » #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017–2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections, 2023)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant d’abord dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes et ce, au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années (2017–2022). Dans la seconde partie, les autrices détaillent les travaux du réseau D!G , lancé en avril 2021 par Vanessa Blais-Tremblay, et présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ». , This article profiles five organizations that have been advocating for equity in Quebec music since 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL and D!G Différences et inégalités de genre dans la musique au Québec. In line with a long tradition of critical work in feminist historiography, the authors first account for the diversity of feminist mobilizations in Quebec music beyond the #metoo “waves” which have received significant media attention over the past five years (2017–2022). In the second part, the authors detail the development of the D!G network, a feminist collaborative research partnership launched in April 2021 by Vanessa Blais-Tremblay, and its contributions to both Quebec’s music industry and to feminist partnership research epistemologies and methodologies.
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Plus jamais silencieuses : essai d'activisme social contre l'oppression de genre par la réalisation d'une oeuvre vidéographique documentaire et participative - Pierret, Caroline (Université du Québec à Montréal, 2023)
Tenant compte de l’émergence de la parole et de l’écoute libérées par les médias sociaux lors des mouvements MeToo et de la séquence de dénonciations d’agression à caractère sexuel qui s’ensuivit au Québec comme ailleurs en Occident, comment aujourd’hui un projet artistique peut-il participer à l’affranchissement de la parole et du visage des femmes? Ce mémoire-création explore les notions de silenciation et d’invisibilisation des femmes, en même temps que les possibilités pour elles de s’en libérer en reprenant contact avec leur puissance, notamment par un usage conscient des instruments médiatiques que sont le cinéma, la vidéo, la photographie et la transmission audio. Il décrit différentes méthodologies testées par la réalisation de projets au cours du programme de maîtrise, tous cherchant à comprendre comment, par la captation de voix et de visages, il est possible d’offrir aux femmes une opportunité de réappropriation de leur pouvoir individuel et collectif. Cette recherche-création culmine dans une installation vidéographique documentaire réalisée en collaboration avec dix-neuf Montréalaises originaires de dix pays différents, qui permet de faire vivre aux personnes spectatrices une expérience de rencontre et de leur faire prendre conscience du trouble qui habite l’intérieur des femmes, et ainsi possiblement le leur. Ce faisant, l’oeuvre pose la question cruciale de ce que nous ne voyons pas, n’entendons pas, ne ressentons pas ou n’avons jamais voulu voir, entendre ou ressentir. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : vidéo, documentaire, femmes, silence, parole, écoute, metoo, féminisme, activisme, agentivité.
Keywords: À ajouter

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023-2026 entre la Guilde des musiciens et musiciennes du Québec et l'Orchestre l'Agora (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023 - 2027 entre la Guilde des musiciens et musiciennes du Québec et l’Orchestre symphonique du Saguenay-Lac-Saint-Jean (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Plan d'action pour les ressources humaines en culture 2023-2028 (Compétence Culture, 2023)

Progress Pride Committee (ACTRA National, 2023)
ACTRA National is proud to be launching the ACTRA National Progress Pride Committee. The inaugural Committee meeting took place on Friday, May 26th, 2023. Mandate The mandate of the committee is to address issues that impact the Queer ACTRA membership across the country, and to build a National community through the sharing of relevant information […]
Keywords: Bibliographie; Dans le rapport

Rebâtir (2023)
Consultation juridique sans frais pour les personnes victimes de violence sexuelle et de violence conjugale.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Réseau d'aide aux hommes pour une société sans violence (À coeur d'homme, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Women's Committee (ACTRA National, 2023)
The best initiatives are driven by members. By getting to know the membership and listening to your experiences, we can better shape initiatives that support you. Does your ACTRA Branch have a Women’s Committee? Find out by contacting your Branch office or contact the National Women’s Committee if you would like to get one started. […]
Keywords: Bibliographie; Dans le rapport

ACTRA By-Laws - ACTRA (2023)
Keywords: Coffre à outils; À ajouter

Harcèlement et inconduites dans le milieu artistique. Quel est mon rôle ? - ADISQ; RIDEAU (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association nationale des éditeurs de livres (ANEL) (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association québécoise de l'indusstrie du disque, du spectacle et de la vidéo (ADISQ) (2023)
Keywords: Bibliographie; Nettoyer

Believability: sexual violence, media, and the politics of doubt - Banet-Weiser, Sarah; Higgins, Kathryn Claire (Polity Press, 2023)

Unsafe words: queering consent in the #MeToo era - Buggs, Shantel Gabrieal; Hoppe, Trevor (Rutgers University Press, 2023)
"What can the #MeToo moment teach queers about consent? And what can queers teach the rest of the world about ethical sex? This radical book brings together academics, activists, artists, and sex workers to tackle dangerous questions about sex, power, consent, and harm.While the authors in this volume are committed to promoting consensual, pleasurable sex, we reject heteronormative, one-size-fits-all models of consent and sexual ethics.#MeToo ushered in an era of reckoning and accountability for one powerful man after another. But too often it has defined sex and harm in starkly heterosexual-and often white and wealthy-terms."Unsafe Words" tells a queerer side of the #MeToo story. Not all of us seek safety in sex. Nor do we all believe "enthusiastic" models of consent are practical or appropriate for some queer communities. We look instead to the tools queer communities have developed themselves to practice ethical sex-from the sex worker negotiating with her client to the gay man having anonymous sex in the backroom. We also consider how queers can better respond to sexual violence. How can our communities do better at responding to and preventing sexual violence?This challenge is especially daunting in a world where the only recourse made available is typically law enforcement, a pillar of American racism, transmisogyny, and homophobia.How can our communities imagine different responses to sexual violence that do not depend on the law to serve justice?The "unsafe words" in this volume challenge dogmatic assumptions about sex and consent while exploring tools and language to promote better, more ethical, and more pleasurable sex for everyone"-- Provided by publisher

3 M$ à Juripop pour venir en aide aux victimes de harcèlement et de violence dans le milieu culturel - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2023)
Keywords: Bibliographie; Dans le rapport; Nettoyer

The other #metoos - Cheema, Iqra Shagufta (Oxford Studies in Gender and International Relations, 2023)
"To bring more awareness to the revolutionary international impact of #MeToo, The Other #MeToos brings together chapters that look at specific iterations of the #MeToo movement across multiple communities, cultures, and countries. Going beyond gender, the book takes into account the intersectional assemblage of location, history, religion, ethnicity, race, class, and neoliberal aspects that inform #MeToo and its place in local and transnational feminisms. From Egypt, Lebanon, Iran, Tunisia, and Morocco to India, Pakistan, Bangladesh, Nepal, and Sri Lanka to South Africa to Latin America to South Korea, Japan, and China to Czech Republic - #MeToo has inspired local movements and hashtag trends as well as transnational and collective hashtags like #MosqueMeToo. Therefore, by making feminism mainstream, it has rendered possible international feminist solidarities unlike any other feminist movement that precedes it. It is critical to document this defining feminist moment of #MeToo and its variants to acknowledge the diversity and multidimensionality of transnational feminisms, along with looking at the various ways they have been changed by the #MeToo, internationally. To that argument, the contributions in this collection examine, analyze, and interrogate the reception, translation, and adaptation of #MeToo in their local, indigenous, minoritized, othered, and/or postcolonial contexts. Overall, The Other #MeToos highlights the adaptation, translation, and impact of #MeToo in non-Western, postcolonial, minoritized, and othered locales to expand the larger discourse and praxes of the #MeToo movement beyond its Americentric focus to explore other feminist possibilities that the movement has enabled"--
Keywords: Feminism; MeToo movement; Sexual harassment of women

Porter plainte: récit - Clermont-Dion, Léa (Le Cheval d'août, 2023)
"Agressée sexuellement par son patron à l'âge de dix-sept ans, Léa Clermont-Dion décide, près d'une décennie plus tard, de poursuivre l'agresseur en justice. Elle consignera son expérience dans son journal jusqu'au procès. Pendant ce temps, l'affaire Harvey Weinstein déclenche le mouvement #MeToo, et des millions de femmes dénoncent la culture du viol à visage découvert. La déposition criante de vérité de Porter plainte témoigne de la froide autorité du droit et des luttes des victimes de crimes sexuels, qui reprennent la parole qu'on leur a soustraite"--Back cover
Keywords: Bibliographie; Nettoyer

Les premier·ères coordonnateurs et coordonnatrices d’intimité certifié·es du Québec - Coordination d'intimité Québec (ICCQ, 2023)
Les coordonnateurs et coordonnatrices d'intimité pour le cinéma et la télévision. Formé·e·s par les programmes de certification qui ont établi le standard du rôle à l'international et ailleurs au Canada, Mo Matton, Stephanie Breton et Mimi Côté représentent la branche du Québec d'Intimacy Coordinato
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Mettre fin au harcèlement sexuel dans le cadre du travail : Se donner les moyens pour agir - Cox, Rachel; Gesualdi-Fecteau, Dalia; Laflamme, Anne-Marie (Comité chargé d'analyser les recours en matière de harcèlement sexuel et d'agressions sexuelles au travail, 2023)
Keywords: Bibliographie; Nettoyer

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

Faire justice: moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Deck Marsault, Elsa (La Fabrique éditions, 2023)
Keywords: Bibliographie; Nettoyer; Restorative justice; Sexual minorities; Violence against; Women

Bureau d'intervention et de prévention - École nationale de cirque - Montréal (École nationale de cirque, 2023)
Le BIP de l'ÉNC vise à prévenir et intervenir en cas de discrimination, de harcèlement et de violence au sein de son établissement.
Keywords: Sophie-Anne

Pollitique contre le harcèlement et l’intimidation et la promotion d’un environnement sain - École nationale de théâtre du Canada (Département du bureau de la direction générale, 2023)
Keywords: Bibliographie; Nettoyer

SPEAK OUT: together for a safer circus - Fédération européenne des écoles de cirque (FEDEC); JUMP (2023)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"--
Keywords: Bibliographie; Nettoyer

Between denunciations and precautions: the #Metoo movement in Quebec. A Critical Discourse Analysis of Quebec newspaper coverage in 2020 and 2017 - Glorieux, Charlotte (Université Charles, 2023)
Keywords: Bibliographie; Nettoyer

Campagne de sensibilisation : Harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2023)
GAIHST Inc est un organisme communautaire de la province de Québec qui vient en aide aux travailleurs et travailleuses ayant subi du harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Répertoire des formations de groupe - Groupe de recherche et d’intervention psychosociale (2023)
«Les formations qu’on offre s’adressent principalement aux professionnel.le.s des milieux scolaires, secondaires et postsecondaires et aux professionnel.le.s de milieux variés où l’information sur les drogues est pertinente (milieux festifs, milieux d’intervention, etc.). Elles peuvent également être offertes directement à la population étudiante des milieux d’éducations postsecondaires (Formation générale aux adultes, formation professionnelle, collégiale ou universitaire). L’approche employée dans la création et l’offre de formation est toujours celle de réduction des méfaits. Nos formations abordent des thèmes tels que les violences à caractère sexuel, le consentement, les effets des substances, la prévention et la réduction des méfaits, les bandelettes de détection de Fentanyl et Naloxone, l’intervention en milieu festif, les drogues et la performance académique, ainsi que de nombreux autres sujets pertinents. »

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Étude sur l’expérience des adultes ayant reçu des services dans le cadre d’un processus judiciaire : Dossiers judiciarisés entre juillet 2020 et juin 2022 au Québec concernant une infraction commise dans un contexte de violence conjugale ou sexuelle - Institut de la statistique du Québec (2023)
Keywords: Bibliographie; Nettoyer

Accueil - Juripop (L'Aparté, 2023)
L'Aparté offre des services juridiques gratuits à toute personne ayant vécu du harcèlement dans le milieu de la culture partout au Québec
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collectif social collective - Le Collectif social (Lutte contre les violences sexuelles, 2023)
Offrent des formations sur mesure, ainsi que les formations : - Prévenir la violence sexuelle dans les événements festifs ou sociaux - Les violences sexuelles chez les communautés LGBTQIA2S+ - Devenir un témoin actif
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Check tes chums - Massé, Manon (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Stratégie en matière de justice autochtone : Ce que nous avons appris Phase 1 de la mobilisation dirigée par le ministère de la Justice Canada - Ministère de la justice Canada (2023)
Keywords: Bibliographie; Nettoyer

Que reste-t-il de nos humours ?À la recherche d’un rire de gauche - Quemener, Nelly (Revue du Crieur, 2023)
Les enjeux liés aux luttes menées par les personnes trans’ sont une parfaite illustration du fait que la visibilité ne suffit pas et qu’elle peut même parfois se révéler préjudiciable. En effet, depuis quelques mois, la presse, la télévision, la radio s’agitent dès qu’une actualité touche de près ou de loin à la transidentité. Actuellement, les voix des trans’ sont encore trop souvent couvertes par les discours cis’, lesquels tendent également à délégitimer les savoirs produits par et pour des trans’. Il est grand temps de retourner la lunette : au lieu de scruter les personnes trans’ – leur transition –, il est urgent de les lire et de les écouter. Ces expériences-là ont certes des choses à apprendre aux personnes cis’ : bien sûr que l’on comprend mieux ce qu’est le genre face à des personnes qui ont fait l’expérience de quitter celui qui leur a été assigné à la naissance, bien sûr que cela rend plus insupportable encore la rigidité des normes de genre, binaires et arbitraires jusqu’à l’absurde. Mais au-delà de ce que les cis’ peuvent apprendre des trans’ pour mieux se comprendre elles-mêmes et eux-mêmes, au-delà de cette lecture instrumentale, il s’agit désormais de laisser les marges parler. Il s’agit de se concentrer sur les luttes sociales, les revendications portées par les personnes trans’ et les associations, de défendre les conditions matérielles d’existence des trans’, de lutter contre les nombreuses discriminations qui pèsent encore sur elles et eux, y compris contre celles qui limitent drastiquement leur accès aux positions permettant de produire légitimement du savoir, il s’agit de les laisser libres de définir leurs cadres de pensée et la manière dont ils, elles, iels souhaitent parler ou pas de leurs parcours. De les laisser, enfin, écrire leur histoire.

Les pratiques des directrices l'industrie de la musique au Québec pour naviguer entre les exigences multiples de leurs fonctions - Saucier, Myriam (Université du Québec à Montréal, 2023)
Keywords: Bibliographie; Nettoyer

En réponse à : « Check ton verre » - Scène & Sauve (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

POLITIQUE ÉDI (ÉQUITÉ, DIVERSITÉ, INCLUSION) - Télé-Québec (2023)
Keywords: Coffre à outils; À ajouter

#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina

Comedy’s double killjoy: workers’ DIY strategies to address harassment and precarity in the comedy industry - Trusolino, Madison; Ships, Diandra (Feminist Media Studies, 2023)
Since 2017, the #MeToo movement has highlighted gender-based violence and harassment in the comedy industry, where those comedians affected have little to no workplace infrastructure to lean on. Because comedy clubs are described as venues rather than sites of work, comedy workers are not technically employees and are not protected by workplace safety laws nor supported by professional organizations or unions. We argue that the lack of a formal workplace and its related precarity exacerbates violence against women, queer, transgender, disabled, and/or workers in the Canadian and American comedy industries, pushing comedy workers to enact do-it-yourself workplace safety strategies to protect themselves and one another. We describe these protective, caring activities as akin to Brenda Parker’s “double killjoy,” and push our understanding of creative work into places of public resistance and life-making.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Now About All These Women in the Swedish Film Industry - Wallenberg, Louise; Papadopoulou, Frantzeska; Koskinen, Maaret; Soila, Tytti (Bloomsbury Academic, 2023)
In the aftermath of the MeToo movement, during an ongoing pandemic, and in the midst of repeated demands for a 50/50 split between men and women in above-the-line positions, this book analyzes and interrogates the politics of gender focusing on the Swedish film industry, often considered to be the most "gender equal" film industry worldwide. While this gender equality (with a considerable proportion of women behind the camera) is much due to policies carried out of the state funded Swedish Film Institute, women filmmakers in Sweden still struggle with the same problems as do women in other national film industries. These problems entail having smaller production and distribution budgets than men and working in an environment involving recurring scandals of gender discrimination and sexual harassment. This open access book looks behind the statistics and explores the often complex cultural, legal, and political conditions under which women have entered a male-dominated industry and discusses women’s strategies and efforts to promote change while providing evidence on how women’s presence has challenged the industry by provoking critical reactions and introducing new ways to portray women on screen. Using a wide range of different sources (e.g. archival material, laws, contracts, films, biographical materials, and interviews), the book tells the history of the rise of gender equality efforts undertaken by the Swedish Film Institute and investigates women’s possibilities to manage the rights to their work. It offers compelling portraits of pioneering women who have worked in or in relation to the industry and looks at the experiences of women currently working in the film industry. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Örebro universitet.
Keywords: Irina; Metoo; Sweden; Swedish Film Institute; TV & radio::APF Films; change; cinema::APFA Film theory & criticism; cinema::APFN Film: styles & genres; conditions; discrimination; equality; film industry; filmmakers; male-dominated; pioneering; politics of gender; rights; scandal; sexual harassment